A spatial explicit vulnerability assessment for a coastal socio-ecological Natura 2000 site - Genua-Olmedo, Ana; Verutes, Gregory M.; Teixeira, Heliana; Sousa, Ana I.; Lillebø, Ana I. (Frontiers in Marine Science, 2023)
In line with the global trend, the Ria de Aveiro coastal lagoon is subjected to multiple co-occurring pressures threatening vital benefits flowing from nature to people. The main objective of this research was to assess the status of habitats important for ecosystem services in the Ria de Aveiro by identifying vulnerable areas to anthropogenic threats. The pressures from seven relevant human activities (recreation, services, aquaculture, agriculture, commercial development, unintended impacts from management, and invasive alien species) were analysed based on their spatiotemporal distribution (exposure) and impact over the EUNIS habitats (EUNIS codes A2.2, A2.22 – sand flats and beaches; A2.3 – mud flats; A2.61 – seagrasses; A2.5, A2.53C, A2.535, A2.545, A2.554 – salt marshes; and, X10 – ‘Bocage,’ a landscape of small-hedged fields) in seven distinct landscape units. A prospective scenario, co-developed for the year 2030, was evaluated using a map-based risk assessment tool and brought forward the near-term vulnerability of the seagrass biotope. The highest risks posed to intertidal habitats (mud flats and salt marshes) were driven mainly by environmental management activities that support critical socio-economic sectors. Our methodology evaluated plausible threats to habitats in the near term, established baseline knowledge for the adaptive management process in Ria de Aveiro Natura 2000 site, and showcased how future assessments can inform the operationalization of ecosystem-based management as new information becomes available.